MEMAHAMI NEGOSIASI PELESTARIAN BUDAYA DAERAH DI INTERNET - Michael H.B. Raditya (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2017)
In globalization era, regional culture that related to the tradition through a difficult phase. The reason that made this thing happen is the explosion of internet media. Internet— either social media or social networking— would be central position to internalizing an influence on society. Not only the society was silenced, various agencies or group from local culture was using internet as their preservation ways. Starting with internet and blogs, to use social networks, such as: facebook, instagram, etc, to promote the preservation that they did. According from displacement of preservation medium, I saw that this thing isn't about change, but there is a negotiation that was created by the group— which they are from tradition culture— with signs on globalization. So, in this article, I would like to discuss about negotiations. Because the internet nearly with media studies, so I try to understand about that negotiation with mediatization theory. I used two methods to answer the question, literate study ana explore media in internet. The results were interesting, negotiations are conducted in shaping patterns of us is different from before. As a result that I got, I hope this article can help the reader to understand the changes and can be maintained the essence of tradition preservation.